2D Basin Modelling and Petroleum System Analysis of the Triassic Play in the Hammerfest Basin of the Norwegian Barents Sea - Ben-Awuah, Joel; Adda, G.; Mijinyawa, A.; Andriamihaja, S.; Siddiqui, N. (2013)
This study seeks to demonstrate the methodology used in 2D basin modelling, enhance the understanding of the Triassic play in the Hammerfest Basin and to show how basin modelling can be used to reduce exploration risk and improve exploration success using the Triassic play in the Hammerfest Basin in the Norwegian Barents Sea as a case study. 2D basin modelling has been done for the Triassic play in the Hammerfest Basin using Petromod software. The play consists of a source rock (Fruholmen formation) of Triassic age, a reservoir (Sto formation) of Middle to Lower Jurassic age and seals of Cretaceous and Upper Jurassic age. Three episodes of erosion (uplifts) in the Late Cretaceous, Paleogene and Paleogene-Neogene have occurred in the basin breaching the integrity of the seal and allowing the escape of hydrocarbons from the trap in some places. These episodes of erosion have increased exploration risks in the Hammerfest Basin and Barents Sea in general. Migration from the source rock into the trap is mainly upwards vertical migration. However, in areas where the hydrocarbons have escaped through the faults at the boundaries of the basin, migration in the layers above the trap is mainly lateral. The hydrocarbons generated are both gas and oil but are predominantly gas. The Upper Jurassic Hekkingen formation in the Barents Sea is a good source rock rich in organic matter with high values of hydrogen index and total organic matter but it doesn't seem to be matured in the Hammerfest Basin.